Understanding the Role of Orexin Neuropeptides in Drug Addiction: Preclinical Studies and Translational Value - Matzeu, Alessandra; Martin-Fardon, Rémi (Frontiers in Behavioral Neuroscience, 2022)
Orexins (also known as hypocretins) are neuropeptides that participate in the regulation of numerous physiological functions, including energy metabolism, homeostasis, sleep, feeding, stress responses, arousal, and reward. Particularly relevant to the scope of the present review is the involvement of the orexin system in brain mechanisms that regulate motivation, especially highly motivated behavior, arousal, and stress, making it an ideal target for studying addiction and discovering treatments. Drug abuse and misuse are thought to induce maladaptive changes in the orexin system, and these changes might promote and maintain uncontrolled drug intake and contribute to relapse. Dysfunctional changes in this neuropeptidergic system that are caused by drug use might also be responsible for alterations of various physiological functions, such as feeding behavior and the sleep-wake cycle that are commonly disrupted in subjects with substance use disorder. Drug addiction has often been associated with an increase in activity of the orexin system, suggesting that orexin receptor antagonists may be a promising pharmacological treatment for substance use disorder. Substantial evidence has shown that single orexin receptor antagonists that are specific to either orexin receptor 1 or 2 can be beneficial against drug intake and relapse. Interest in the efficacy of dual orexin receptor antagonists, which were primarily developed to treat insomnia, has grown in the field of drug addiction. Orexins play important roles in a wide range of physiological functions. Treatments that target the orexin system may be a promising strategy to reduce drug intake, mitigate relapse vulnerability, and restore “normal” physiological functions, including feeding and sleep. The present review discusses preclinical and clinical evidence of the involvement of orexins in drug addiction and possible beneficial pharmacotherapeutic effects of orexin receptor antagonists to treat substance use disorder.